The promise and peril of Australian climate leadership under Albanese. Issue 1 (2nd January 2023) - MacNeil, Robert; Edwards, Gareth A. S.
Abstract: After nearly a decade of policy inaction by the Abbott/Turnbull/Morrison Coalition governments, the election of Anthony Albanese's Labor government has ushered in expectations of a sea-change in Australian climate policy, one that might allow the country to finally emerge as a global leader on the issue. Yet while years of inaction have left some relatively easy victories for the new government to rack up, the change of leadership and rhetoric obscures some key continuities in the Albanese government's approach that need to be foregrounded and critiqued by domestic and international audiences alike. In this brief commentary, we consider what the new Labor government might mean for Australian climate action over the coming years. We focus, in particular, on the role that fossil fuel exports will continue to play in overwhelming any emissions cuts achieved domestically, and underscore the need for a much broader and more ambitious national climate strategy designed to wean the country off its reliance on coal and gas revenues.